Efforts to Increase Legal Awareness in Preventing Moral Degradation of Sawan 1 Public High School Students in Buleleng Regency Regarding Pornography and Sexual Violence Cases - Yuliartini, Ni Putu Rai; Mangku, Dewa Gede Sudika (Institute of Education and Social Research, 2024)
The phenomenon of moral degradation among students, especially related to cases of pornography and sexual violence. SMA Negeri 1 Sawan, which is located in Buleleng Regency, faces challenges related to the moral degradation of students due to cases of pornography and sexual violence. The problem is that there is a pornography case which contains obscene/pornographic scenes of two students from SMA N 1 Sawan, Buleleng Regency, there is an issue that a perverted/pornographic video of two students from SMA N 1 Sawan, Buleleng Regency is widely spread on social media, including among students at SMA N 1 Sawan, other Buleleng Regency, and the school also shows that the potential for pornography and sexual violence at SMA N 1 Sawan is still quite high. The aim of this article is to strengthen character education and increase legal awareness of SMA N 1 Sawan students. The method used is a ball pick-up system. The results show that efforts to increase legal awareness have been carried out according to plans and methods, the target community has benefited in the form of increased understanding or knowledge of SMA N 1 Sawan students as the target community regarding the legal traps of perpetrators of pornography and sexual violence among teenagers.